Structural Equation Approach to Analyze Cyclists Risk Perception and Their Behavior Riding on Two-Lane Rural Roads in Spain - Griselda López (Sustainability, 2021)
The use of bicycles on two-lane rural roads in Spain has been increasing in recent years. However, these roads have no bicycle infrastructure, being cyclists forced to share the road and interact with motorized vehicles. In rural environments, the interaction between road users from the cyclist’s point of view is still not well understood. To analyze it, the relationships between risk perceptions and behavioral factors of rural cyclists according to their demographic characteristics, profile, and self-reported knowledge on traffic rules were obtained. An online survey was used, which collected the opinion of 523 cyclists. Data were analyzed by using structural equation models. The Thurstonian Item Response Theory approach was adopted to include raking responses. Different perceptions among demographic groups were found. Younger cyclists present the lowest risk perception while having a higher risk behavior. The knowledge about traffic rules was correlated with safety behavior, showing the importance of this factor. These results are in line with urban cycling. However important differences under risk elements for rural cyclists, mainly associated with potential hazards on the shoulder, have been drawn. These findings may help policy makers to integrate cycling with vehicular traffic on two-lane rural roads in a safe way.